Parametric Study of the Borehole Drilling in Jointed Rock Mass. (30th September 2021) - Gao, Yanan; Zhang, Yudong; Zhang, Zetian; Li, Minghui; Sun, Yingfeng; Lan, Donghao; Gao, Feng
Abstract : Gas is associated with coal mining; it commonly exists in the coal seam. It is one of the major dangers during the production because its reaction between the coal masses may induce the gas-coal outburst as well as it being an expositive matter. The gas accident has caused a huge amount of property damage and casualties. Therefore, the primary precaution for coal mining is gas control. At present, drilling and extraction are the main approaches for gas accident prevention. After drilling, the ground pressure will be released; the gas which is in a free state or absorbed in the coal seam will be easy to extract as the migration channel is enhanced. Hence, one of the most concerned problems is the stress redistribution of the coal and rock mass around the borehole. In practical engineering, there are many joints distributed in the coal and rock strata, so it is necessary to investigate the effect of the drilling in the jointed coal and rock mass. In this paper, the boundary element model of the borehole in the jointed coal and rock mass is established to study the influence of joints on the stress and displacement field. The following results can be obtained. The number of joints has a significant effect on the maximum displacement of the coal and rock mass. The maximum displacement increases with the number of the joint. The position of the maximum displacement shifts from the boundary of the borehole to the far field. Meanwhile, it can be found that the displacement may reach a peak value when the joint angle is 30° and if the joint number is less than 4, and the maximum displacement may occur under the joint angle of 45° and if the joints number continuous increases. The von Mises stress has a trend of increasing with the number of joints when the joint angle is less than 30°, while it has a decreasing trend when the joint angle is larger than 30°. The max stress may occur at the joint angle of 15°. The maximum shear stress occurs mostly in the No. 4 joint and the No.7 joint. When the joint angle is 30°, the maximum shear stress occurs in the No. 3 joint and the No. 4 joint. The overlap of the position of the maximum von Mises stress or the maximum displacement with different joint angles or different numbers of joint leads to a reexploration of such positions. The position of the maximum von Mises stress and the maximum displacement o is relatively steady, which locates symmetrically around the borehole. The line between the points that behaves as the maximum von stress is approximately perpendicular to the joint direction.